2017
DOI: 10.1038/leu.2017.276
|View full text |Cite|
|
Sign up to set email alerts
|

Mutant JAK3 phosphoproteomic profiling predicts synergism between JAK3 inhibitors and MEK/BCL2 inhibitors for the treatment of T-cell acute lymphoblastic leukemia

Abstract: Mutations in the interleukin-7 receptor (IL7R) or the Janus kinase 3 (JAK3) kinase occur frequently in T-cell acute lymphoblastic leukemia (T-ALL) and both are able to drive cellular transformation and the development of T-ALL in mouse models. However, the signal transduction pathways downstream of JAK3 mutations remain poorly characterized. Here we describe the phosphoproteome downstream of the JAK3(L857Q)/(M511I) activating mutations in transformed Ba/F3 lymphocyte cells. Signaling pathways regulated by JAK3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
96
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(99 citation statements)
references
References 45 publications
3
96
0
Order By: Relevance
“…Further, combining these two inhibitors in vitro, achieved a synergistic effect demonstrating a greater increase in apoptosis and a decrease in proliferation compared to either inhibitor alone. This data confirmed findings previously demonstrated in T-ALL (20,35,36) and other cancers. (37)(38)(39) Ruxolitinib treatment alone has been considered a breakthrough therapy for myeloproliferative neoplasms but long-term studies have shown that this treatment is not curative and does not lead to molecular or pathological remission.…”
Section: Discussionsupporting
confidence: 92%
“…Further, combining these two inhibitors in vitro, achieved a synergistic effect demonstrating a greater increase in apoptosis and a decrease in proliferation compared to either inhibitor alone. This data confirmed findings previously demonstrated in T-ALL (20,35,36) and other cancers. (37)(38)(39) Ruxolitinib treatment alone has been considered a breakthrough therapy for myeloproliferative neoplasms but long-term studies have shown that this treatment is not curative and does not lead to molecular or pathological remission.…”
Section: Discussionsupporting
confidence: 92%
“…JAK3 mutations were the most recurrent genomic aberration affecting JAK/STAT genes in this meta-analysis with a hotspot mutation rate of 36.4% (literature: 21% [12]-71% [17]). The oncogenic potential of the most frequent JAK3 mutation M511I as well as the less frequently occurring mutations A573V and V674A was shown in various systems: M511I, A573V, as well as V674A mutant cell lines demonstrated high phosphorylation of STAT5 and ERK, leading to cytokine independent growth [39,40]. When transplanting mice with bone marrow progenitor cells harboring the M511I or A573V mutation in JAK3, they develop a T-ALL-like disease, characterized by an expansion of immature CD8 + T-cells.…”
Section: Moreover Constitutive T-cell-receptor or Cytokine Input Of mentioning
confidence: 99%
“…Moreover, ruxolitinib inhibited JAK-STAT signaling and abrogated the hyperactivation effect of IL-7 and was highly effective in these preclinical models [41]. Finally, signaling pathways with altered phosphorylation after JAK inhibition (MEK, PI3K) and BCL2 can be pharmacologically inhibited, which results in synergistic antitumor effects in combination with JAK kinase inhibitors in primary T-ALL samples with JAK3 mutations [42]. …”
Section: Targeting the Jak/stat Pathwaymentioning
confidence: 99%